PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PEREDARAN OBAT TANPA IZIN EDAR : (Studi Putusan Nomor 1/Pid.Sus/2023/Pn.Pre) - Astuti, Tri; Purwanda, Sunardi; Prasisto, Johamran; Prayudi, Prayudi (Prodi Magister Ilmu Hukum Fakultas Hukum Universitas Singaperbangsa Karawang, 2024)
This research aims to find out the legal arrangements related to the unlicensed drug trade, which is reviewed from Law Number 36 of 2009 concerning Health or called the Health Law. In addition, this research also finds out about law enforcement related to the criminal act of unlicensed drug distribution in case verdict Nomor: 1/Pid.Sus/2023/Pn.Pre. The type of research used is normative research combined with empirical research. This research uses a statutory approach related to legal norms or substance, legal principles, legal theories, legal arguments combined with research that directly observes events that occur in the field. The results showed that legal arrangements related to the unlicensed drug trade are regulated in Articles 196, 197 and 198 of the Health Law. The form of law enforcement carried out regarding the distribution of unlicensed drugs in the case of the decision is repressive, which finds the application of sanctions for violators. These sanctions also provide a deterrent effect so that similar violations do not occur again in the future and ensure that justice is upheld.